Stainless steel selection tool for water application: pitting engineering diagrams - Hägg Mameng, Sukanya; Wegrelius, Lena; Hosseinpour, Saman (Frontiers in Materials, 2024)
This work systematically investigates the effect of chloride level, temperature, and the water system's oxidative power on the pitting corrosion performance of stainless steels in pH-neutral environments. Two test programs were set to a) develop a robust method for constructing the pitting engineering diagrams and b) construct the pitting engineering diagrams based on the obtained method from the first test program. The various electrochemical techniques were selected to permit and understand factors that affect the corrosion behavior of stainless steel. Extensive testing has been performed with shortterm electrochemical measurements and long-term immersion tests. The obtained result demonstrates that the electrochemical methods were sufficient to define pitting diagrams showing the boundaries between pitting and no pitting as a function of chloride concentration, temperature, and the water system's oxidation potential. The laboratory long-term electrochemical test results correspond the best to real applications and clearly underline the importance of an induction time for pit initiation. Two different types of pitting engineering diagrams have been constructed based on the water system's oxidation potential. The open circuit potential (EOCP) of 150 mV vs saturated calomel electrode (SCE) corresponds to simulating sterile tap water, whereas EOCP of 400 mV vs SCE corresponds to slightly chlorinated water or water with some biological activity. Pitting engineering diagrams are a very useful tool to aid material selection. However, it is important to realize that additional factors, such as different surface conditions and the presence of other environmental species, crevice design, or weld will affect the exact position of the boundaries between pitting and no pitting.